Suitability of temperature, hydraulic heads, and acesulfame to quantify wastewater‐related fluxes in the hyporheic and riparian zone. Issue 1 (28th January 2013) - Engelhardt, Irina; Prommer, Henning; Moore, Catherine; Schulz, Manoj; Schüth, Christoph; Ternes, Thomas A.
Key Points Fate of acesulfame is assessed in a complex hyporheic zone setting Its value as wastewater tracer is determined through data worth analysis Recorded temperatures provided the most valuable constraints to quantify fluxes